PERANCANGAN SISTEM INFORMASI PERSEDIAN STOK BARANG PADA GROSIR IJUL BERBASIS WEB - Dwika Fazlina; Sondang (Cemara Education and Science, 2025)
Stock inventory management at Ijol wholesale is an important aspect in maintaining smooth operations and customer satisfaction. This research aims to design and implement a web-based stock inventory information system for Ijol Wholesale. The research method used includes a literature study to understand the basic concepts of inventory information systems, user needs analysis, web-based system design, and implementation and evaluation of the developed system prototype.